Academician Ihor Yukhnovskyii: Physicist, Politician, and Not Only... - Mryglod, I.M.; Ivankiv, O.L. (Ukrainian Journal of Physics, 2025)
On September 1, we marked the 100th anniversary of the birth of one of the founders of the restoration of Ukraine’s statehood in the late 1980s and, during the difficult 1990s, an outstanding Ukrainian scientist, the founder of the modern Lviv school of statistical physics, Professor, Academician of the National Academy of Sciences of Ukraine, the full and honorary member of the Shevchenko Scientific Society Ihor Yukhnovskii. At the end of his complicated and eventful life, he reflected, “Now I don’t know what was most important to me in my life: physics or politics?” Let us also reflect on this question.